Knowledge about risk factors for cancer and cancer risk behavior among patients with severe mental illness. Issue 12 (21st September 2021) - Grassi, Luigi; Caruso, Rosangela; Biancosino, Bruno; Belvederi Murri, Martino; Riba, Michelle; Meggiolaro, Elena; Ruffilli, Federica; Palagini, Laura; Nanni, Maria Giulia; Zavatta, Sara; Toffanin, Tommaso; Folesani, Federica; et al.
Abstract: Objective: To examine knowledge about, perception of and current risk factors for cancer, among patients with severe mental illness (SMI) and to compare these variables with patients without SMI. Methods: A series of patients affected by SMI (i.e., schizophrenia spectrum disorders, bipolar disorders and severe personality disorders) and a matched (gender, age) control group of primary care attenders were assessed, by using an ad hoc semi‐structured interview and a short true/false 17‐item questionnaire, about family history of cancer, cancer risk‐related lifestyles, personal perception and knowledge of risk for cancer. Results: Patients with SMI ( n  = 185, mainly schizophrenia spectrum disorders, 48%, and mood disorders, 33%) significantly differed from primary care attenders ( n  = 173) for: lower participation to occult stool blood screening test, Pap smear test and mammography; higher prevalence of current and past smoking habits; lower awareness towards their own physical symptoms and their perception of risks for cancer; lower physical exercise practicing; lower knowledge about risk factors for cancer (e.g. familiarity for cancer, smoke‐habits, breast and uterine cancer). Conclusions: Patients suffering from SMI had higher at‐risk behavior for cancer and showed fewer concerns and less knowledge about risk for cancer than primary care attendees. These findings can guide to implement screening for cancer (e.g., Pap test, blood) and to design evidence‐based interventions to reduce cancer risk (e.g., educational and behavioral change for smoking cessation, dietary habits) among patients with SMI.